Literature Review: Hubungan Preferensi Makanan dan Pengetahuan Food Waste dengan Perilaku Food Waste - Risqy Karima (Pusat riset dan Inovasi Nasional, 2026)
Food waste is a global issue that has a major impact on the economy, environment, and food security. The high rate of food waste is directly influenced by food waste behavior. Also, food waste behavior does not just appear, but it is supported by other factors such as food waste knowledge and food preferences. As an effort to prevent the increase in food waste, it is important to know the relationship between these two factors and the occurrence of food waste behavior. The method used is a literature review of open access scientific articles with English language used and published in the period 2015–2025 through the Google Scholar databases. The results of the review show that most studies found a significant relationship between food waste knowledge and food preferences with food waste behavior. However, some studies also showed inconsistent results. Although many studies support the relationship between food waste knowledge and food preferences with food waste behavior, the difference in results also indicates that there are still other factors that are strongly related to food waste behavior, so more comprehensive efforts are needed to reduce the occurrence of food waste behavior.